Radical Scavenger Properties of Some 1,2-Dithiol Compounds Against Electropolymerization of Aniline - HADJADJ*, MOHAMMED; DADAMOUSSA, BELKHIR; ABASQ†, MARIE-LAURENCE; SAIDI, MOKHTAR; BURGOT†, JEAN-LOUIS; DARCHEN‡, ANDRÉ (Asian Journal of Chemistry, 2009)
The kinetics of aniline electropolymerization was investigated inacidic H2O/CH3CN solutions and in presence of some 1,2-dithiol compounds.The reactions were studied under cyclic potential scanning tomeasure the electric charge involved between the redox states of theelectrodeposited polymers. The electrochemical growth of electrodepositswas kinetically dependent upon the dithiol. Generally, in presenceof 1,2-dithiol compounds the growth of electropolymer was slower thanobserved for aniline alone. In the presence of 3-aminophenyl-5-(4-methoxyphenyl)-1,2-dithiol the aniline electropolymerization wasaccelerated and led to an improvement in the conductivity of polymerfilms. In order to establish the nature of the process, aniline electropolymerizationor co-polymerization with the 1,2-dithiol compounds, electrodepositswere prepared on vitreous carbon plates and then analyzed byscanning electron microscopy. The morphology was a fibrillar one andthe analysis showed that sulfur element was inside the electrodeposits.